2020
DOI: 10.1042/bsr20192252
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome survey analysis and microsatellite motif identification of Sebastiscus marmoratus

Abstract: The marbled rockfish Sebastiscus marmoratus is an ecologically and economically important marine fish species distributed along the northwestern Pacific coast from Japan to the Philippines. Here, next-generation sequencing was used to generate a whole genome survey dataset to provide fundamental information of its genome and develop genome-wide microsatellite markers for S. marmoratus. The genome size of S. marmoratus was estimated as approximate 800 Mb by using K-mer analyses, and its heterozygosity ratio and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
(37 reference statements)
7
20
1
Order By: Relevance
“…The types of motifs contained 77.22% (325,450) dinucleotide, 20.38% (85,912) trinucleotide, 2.11% (8,877) tetranucleotide, 0.20% (838) pentanucleotide, and 0.09% (390) hexanucleotide ( Table 3). The percentage of dinucleotide repeats was the highest, and as the repeat motif length increased, the number of loci decreased, similar to other studies (13,24,25). It has been suggested that longer repeats have higher mutation rates, causing instability (26,27) and shorter persistence times because of their downward mutation bias toward a reduction in repeat number (28).…”
Section: Ssr Loci Identificationsupporting
confidence: 84%
See 1 more Smart Citation
“…The types of motifs contained 77.22% (325,450) dinucleotide, 20.38% (85,912) trinucleotide, 2.11% (8,877) tetranucleotide, 0.20% (838) pentanucleotide, and 0.09% (390) hexanucleotide ( Table 3). The percentage of dinucleotide repeats was the highest, and as the repeat motif length increased, the number of loci decreased, similar to other studies (13,24,25). It has been suggested that longer repeats have higher mutation rates, causing instability (26,27) and shorter persistence times because of their downward mutation bias toward a reduction in repeat number (28).…”
Section: Ssr Loci Identificationsupporting
confidence: 84%
“…Genome survey sequencing (GSS) using next-generation sequencing (NGS) is a time-and costeffective way to evaluate genome information, such as genome size, heterozygosity level, and repeat content, and can be used to develop molecular markers (13,14). Simple sequence repeats (SSRs) or microsatellites are short tandem repeats of 1-6 nucleotides that have been utilized as genetic markers because of their outstanding abundance and high variability (15).…”
Section: Introductionmentioning
confidence: 99%
“…The clean reads were assembled into contigs in software SOAPdenovo (v2.01, https://github.com/aquaskyline/SOAPdenovo2/ ) by applying the de Bruijn graph structure [ 26 ]. The paired-end information was then used to join the unique contigs into scaffolds [ 11 ]. To assess the completeness of the assembly, a Benchmarking Universal Single-Copy Orthologs (BUSCO, v.4.0, https://busco.ezlab.org/ ) evaluation was performed using the Eukaryota vertebrata_odb10 database [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…At present, high-throughput next-generation sequencing (NGS) is the main method of genome investigation, which is an important and effective strategy to generate genetic and genomic information [11]. Genome survey sequencing bases on the low-depth sequencing data of the small fragment library [12], and can effectively evaluate the genome size, GC content and heterozygosity through K-mer analysis [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation